APPLICATION OF PROMETHEE II METHOD IN DECISION-MAKING FOR GRANT DISTRIBUTION IN ACADEMIC ENVIRONMENT - Raja Ayu Mahessya; Novi Trisna (Proceedings on Engineering Sciences, 2025)
The PROMETHEE II algorithm is used for multi-criteria analysis in decision-making. This algorithm compares and ranks various choices based on pre-determined criteria. For instance, at UPI YPTK Padang, it is used to recommend final grades for lecturers receiving grants, ensuring these grades align with graduation standards. PROMETHEE II, which stands for Preference Ranking Organization Method for Enrichment Evaluation, addresses the complexity of decision-making involving multiple criteria, providing a more objective and accurate assessment for grant-receiving lecturers. The criteria data for lecturers, including problem formulation, external research, research methods, literature review, and feasibility study, are collected and analyzed using the PROMETHEE II algorithm. The integrated evaluation criteria are analyzed to produce final grades for each grant-receiving lecturer. The results show that PROMETHEE II provides final grade recommendations in line with graduation standards for each lecturer eligible for the grant. These recommendations are based on the performance and contributions of each lecturer in various academic and research activities. The final grades can be used as a basis for decision-making regarding the graduation of grant recipient lecturers. From the analysis of data from seven researchers, three received grants as their net flow values were greater than 0.